On the existence and characterization of unequal exchange in the free trade - Naoki Yoshihara; Soh Kaneko (University of Massachusetts, Department of Economics, 2016)
As in Roemer (1982, chapter 1), this paper considers a simple international trade model and examines the existence and characterization of free trade equilibria involving the unequal exchange of labor (UE). The paper provides an almost complete characterization of the domain of economies in which free trade equilibria with incomplete specialization exist. Moreover, the necessary and sufficient conditions for free trade equilibrium to involve UE is identified. It suggests that the emergence of free trade equilibria with UE cannot be entailed by the competitive mechanism of markets and unequal distribution of wealth alone, but might be understood as an outcome of equilibrium selection on the basis of Nash bargaining between rich and poor nations.
Keywords: D63; D51; 330; Unequal exchange of labor; International division of labor; Subsistence international economies; Internationale Arbeitsteilung; Handelsliberalisierung; Arbeitsmobilität; Faktorproportionentheorem; Marxismus; Theorie